Praktik Berpemerintahan di Desa Hilihati - Verlin Takdir Setiaman Waruwu (CV. ULIL ALBAB CORP, 2024)
This research discusses the Practice of Governing in Hilihati Village (Study of Govermentality in Hilihati Village, Lahewa Sub-district, North Nias Regency, North Sumatra), The results showed that the strong intervention of the supra-village government and prolonged conflict in governance caused the Hilihati Village government to lose its identity as a real government. In addition, in governance, the Hilihati Village government was preoccupied with technocratic matters that did not provide significant benefits for village progress. As a result, the Hilihati Village Government is characterized as an administrative administration that is unable to bring the state into the midst of the community.